2008
DOI: 10.1080/13501760701702272
|View full text |Cite
|
Sign up to set email alerts
|

Norm advocacy: a small state strategy to influence the EU

Abstract: In June 2001 the European Council adopted the EU Programme for the Prevention of Violent Conflict. The story of how conflict prevention became an integral and legitimate part of EU policy and practice illustrates the influence of powerful ideas and successful norm advocacy of a small state managing to punch above its weight in the EU. The aim of this article is to analyse norm advocacy as a potent addition to traditional strategies of gaining influence in the Union. By tracing the process of Swedish promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 25 publications
0
69
0
6
Order By: Relevance
“…However, large countries (in fsQCA: 'large') are generally supposed to be more influential in the Council than smaller ones (Tallberg, 2008) and, in external policies, large States function more autonomously than small States and thus have more room for manoeuvre (Dijkstra, 2011). However, others (Baillie, 1998;Thorhallsson & Wivel, 2006;Björkdahl, 2008) point out that small States can use the Presidency to increase their influence on decision-making in the EU, since they are usually not expected to (be able to) push their interests in the same way as large States do (Vanhoonacker et al, 2010). In any case, it is unclear whether small States have more or less influence than large States during their Presidency (Warntjen, 2007).…”
Section: Conditions For Influencementioning
confidence: 99%
“…However, large countries (in fsQCA: 'large') are generally supposed to be more influential in the Council than smaller ones (Tallberg, 2008) and, in external policies, large States function more autonomously than small States and thus have more room for manoeuvre (Dijkstra, 2011). However, others (Baillie, 1998;Thorhallsson & Wivel, 2006;Björkdahl, 2008) point out that small States can use the Presidency to increase their influence on decision-making in the EU, since they are usually not expected to (be able to) push their interests in the same way as large States do (Vanhoonacker et al, 2010). In any case, it is unclear whether small States have more or less influence than large States during their Presidency (Warntjen, 2007).…”
Section: Conditions For Influencementioning
confidence: 99%
“…If they are to apply to other 'small states,' we must be able to identify which states those are. For this reason, perhaps, there has been a richer conversation when the small states involved are limited to those in Europe (Thorhallsson and Wivel, 2006;Wivel, 2005;Steinmetz and Wivel, 2010;Björkdahl, 2008;Goetschel, 1998;Nasra, 2011;Rickli, 2008;Thorhallsson, 2010;Hey, 2003b;Ingebritsen, 2006;Panke, 2011;Panke, 2010). There, the subfield seems to have progressed, while cumulation and comparison regarding the rest of the world's 'small states' has been less notable.…”
Section: Of Size and Power: The Problem Of Definitionmentioning
confidence: 99%
“…(Adler et al, 2005: 197-198) The majority of normative power work is found spread across Europe, as illustrated by the contributions from the UK (Kent, Oxford and Warwick), Germany (Tübingen), Denmark (Copenhagen) and Turkey (Bahcesehir, Istanbul) in this special issue. This assessment of internationalization is reinforced by normative power scholarship by Christopher Bickerton (2011aBickerton ( , 2011b and Zaki Laïdi (2008aLaïdi ( , 2008b at Science Po, Paris; Annika Björkdahl (2008Björkdahl ( , 2011 in Lund; Tuomas Forsberg (Forsberg, 2011;Forsberg and Seppo, 2009) in Helsinki;Hiski Haukkala (2008 in Tampere; Robert Kissack (2009Kissack ( , 2010 in Barcelona; Mary Martin and Mary Kaldor (Kaldor, 2012;Kaldor et al, 2007;Martin, 2011) at the London School of Economics and Political Science, London; Jan Orbie (2006Michelle Pace (2007;Diez and Pace, 2011) in Birmingham; and Daniela Sicurelli in Trento and Sibylle Scheipers in St Andrews Sicurelli, 2007, 2008;Sicurelli, 2010).…”
Section: Assessing Engagement Internationalization and Comparisonmentioning
confidence: 99%